Exploring comparative research on housing policies in German Cities: a literature review and directions for further research - Fricke, Carola (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
In response to the recurring housing question, municipal decision-makers in German cities developed a variety of local housing policies. In recent years, we correspondingly witness an increase in comparative perspectives which analyze the variation and changes in German urban housing policies and planning instruments. This article, first, reviews research on housing policies in German cities with a particular focus on conceptual debates, comparative methodologies, and case selection. Therefore, the review categorizes academic contributions from geography, policy analysis, and planning studies. The article’s second part revisits approaches from comparative housing studies, comparative urbanism, and policy mobility studies in order to explore the extent to which these perspectives offer complementary lenses for analyzing the geographies of urban housing policies. Thereby, the article proposes new directions for research on inter-urban policy mobility and sites of learning from elsewhere. This entails framing urban policy arenas not as static or isolated, but as embedded in inter-urban processes and networks which contribute to learning processes through knowledge acquisition and best practices.